Ground water recharge from a lined watercourse under shallow water table condition - Goyal, V.; Jhorar, B.S.; Malik, R.S. (Annals of Agricultural Research, 2014)
The study was conducted to quantify the field groundwater recharge dynamics. Rise and fall in water table were observed in observation wells at orthogonal distances X = 5, 25, 50 and 100 m from a 7 year old cement lined channel (Width = 0.6 m, Water depth = 0.37 m, Design discharge = 0.23 m3/s) at different time intervals. The initial water table was at 2.54 m depths from soil surface. The height of the bottom of the watercourse (Ho) from the water table was 2.43 m. Ground water rise R and groundwater fall F increased with time at all orthogonal distances X and followed the square root time law with r2 values more than 0.95 (R = 0.0366 t1/2 + 0.03514; F = -0.0474 t1/2 + 0.0754 for 5 m). The watercourse influencing orthogonal reach (the value of X at which rise is more than 14 % of the total rise at 5 m) was 100 m. Groundwater rise rate RR and falling rate FR decreased with time following inverse square root law with r2 values equals to 0.765 for X=5 m. Seepage from watercourses was mainly a horizontal infiltration phenomenon under shallow water table condition. The ground water rise and fall decreased with distance exponentially with r2 value more than 0.93 (R= 0.4092 e-0.0192 X and F = 0.5505e-0.0114X). Groundwater rise R was higher than groundwater fall up to 100 hours and then the order was reversed i.e. fall was larger than rise at time more than 100 hours. The practical applications are that lined watercourses contribute to the considerable seepage and ground water recharge up to a canal reach of 100 m even in the short time interval of 170 hours.